The relationship between mode of delivery and postpartum depression - Leyla Kaya; Zerrin Çiğdem (Wolters Kluwer Medknow Publications, 2019)
PURPOSE: Postpartum period is a critical interval in which the woman is under risk for psychiatric disorders including postpartum depression (PD). This study was performed to investigate the impact of the mode of delivery on the occurrence of PD in primiparous mothers. MATERIALS AND METHODS: This correlational study was performed on 244 primiparous women (aged 15-49 years) in 17 primary health-care centers. Sociodemographic, obstetric, and PD-related data were gathered using questionnaires and the Edinburgh Postnatal Depression Scale (EPDS) on the 1st and 3rd months after delivery. The questionnaires were administered to all primiparous mothers who were registered to the relevant health-care center. Questionnaires were administered by the researcher for 25-30 min with face-to-face interview technique. RESULTS: Comparison of EPDS scores on the 1st and 3rd months indicated that there was a remarkable decline over time (Z = 11.112, P = 0.001). There was an inverse association between educational level and EPDS scores on the 3rd month (P = 0.037). On the other hand, no significant relationship was detected between age groups, occupation, income, place of accommodation, and EPDS scores. Evaluation of the relationship between obstetric features and EPDS scores revealed that desired and performed modes of delivery, induction, episiotomy, and spinal anesthesia were not linked with EPDS scores. The postpartum behavior (χ2 =10.315; P = 0.035) and feeding method of infants (χ2 =6.109; P = 0.013) were associated with EPDS scores on the 1st month, but not with EPDS scores on the 3rd month. CONCLUSION: Effective measures must be established for early recognition of factors affecting the occurrence of PD. Health planners and policymakers must spend their efforts for promotion of the knowledge and attitudes of mothers during pregnancy. Identification of factors for PD necessitates implementation of multicentric, controlled trials on larger series.